Percepções sociais do aborto provocado: uma explicação em termos de crenças sociais e familiaridade - Santos, Adriana Pereira dos (2015)
For appearing in a question of public health, the induced abortion has been the subject of the social debate. Nevertheless, the discussion is around the speeches that evaluate this behavior not only as a morally inacceptable fact, but also as an action passive of punishment inside the Brazilian legislation. From this reflection, this work analyzed the social perception of induced abortion and its relationship with a whole series of psychosocial factors that make this perception possible. The perception is understood inside three evaluative dimensions: community (how much the action of induced abortion is common), justice (how much the action of induced abortion is fair) and punishment (how much the action of induced abortion must be punished). They were presented stories of abortion in the conditions allowed by law (normalized) and in the not allowed conditions (non-normalized), and also participants who were requested to evaluate them as fair, ordinary and passive of punishment behavior. The considered psychosocial factors were social beliefs that support the social position facing the induced abortion, essentialist beliefs in the differences among men and women, religiosity and familiarity with the induced abortion. For this, it was realized a study correlated to the application of a questionnaire to 614 university students from both male and female sexes from a public university in Paraíba. The results found indicated, for the studied sample, that the induced abortion is perceived as a common behavior, for both situations, normalized (allowed by law) and non-normalized (illegal abortion). The normalized abortion was considered as fairer and less passive of punishment, while the participants considered the non-normalized abortion as less fair and more passive of punishment. As to the position, there was an adhesion to the arguments against the abortion practice, except the arguments linked to the autonomy and individual freedom of the woman to decide about her own body. The sample admitted a small familiarity with the phenomenon of abortion. In the perception of the abortion community (normalized and non-normalized), the explained variations were the position and the familiarity. But for the perception of the justice (normalized and nonnormalized) and the perception of the normalized punishment, the explained variations were the position and the religiosity. And for the perception of the non-normalized punishment, only the position appeared as an explained variation. It was observed that the essentialism does not appear as an explained variation of any perception. The results point to the fact that the more familiarity with the phenomenon of abortion the more is the attribution of the community, it is, there is the recognition of the raised occurrence of abortions for those who admit some type of proximity with the question. It makes sense then to strengthen the institutional role as promotional of the visibility of the abortion, to go beyond the perspective of the morality, but for the social problematic that it is involved with, while behavior daily practiced to the default of the moral judgments made by it.